The eight-year long-term follow-up on the effectiveness of the quadrivalent human papillomavirus vaccine in Chinese women 20-45 years of age. Issue 5 (30th November 2022) - Zhao, Chao; Zhao, Yun; Li, Jingran; Li, Mingzhu; Su, Yanyan; Mi, Xin; La Tu, Su Yi; Shen, Danhua; Ren, Lihua; Li, Yanyan; Wang, Linhong; Wei, Lihui
ABSTRACT: The quadrivalent human papillomavirus (4vHPV) vaccine has shown confirmative effectiveness in preventing HPV-related diseases among women and men around the globe. The phase III, randomized, double-blind efficacy study (Base study, NCT00834106) conducted in China showed 100% efficacy against HPV 16/18-related cervical intraepithelial neoplasia and efficacy against HPV persistent infection for 78 months. Participants aged 20–45 years who received three doses of 4vHPV vaccine or placebo during the base study were selected and invited for this long-term follow-up (LTFU) study to assess the long-term effectiveness of the 4vHPV vaccine in preventing HPV-related diseases. A total of 368 participants were included in this LTFU study with a median follow-up of 94 months. Among 27 participants (Vaccine vs. Placebo: 8 vs. 19) who underwent colposcopy and biopsy due to cervical cytological abnormalities or HPV infection, no HPV-16/18-related cases of cervical intraepithelial neoplasia (CIN), vulvar intraepithelial neoplasia (VIN), or vaginal intraepithelial neoplasia (VaIN) was observed in the vaccine group while two HPV-16-related cases (CIN1/VaIN) were observed in the placebo group. There were another two HPV-related cases (non-vaccine HPV types) found in the placebo group. Consistent with the findings from global studies that suggested long-term efficacy of 4vHPV vaccine, our study showed continued protective effect of 4vHPV vaccine against HPV-related precancerous diseases through a median follow-up time of 94 months with the longest follow-up time of 125 months after completing three doses of vaccination among Chinese women 20–45 years of age.